Meningkatkan Partisipasi Anggota Koperasi Mahasiswa Al-Hikmah Melalui Pengetahuan dan Motivasi Perspektif Syariah - Arifah Nailah; Meisha Maulidiya; Lena Oktaviona; Suryani Suryani; Wazin Wazin; Jamaluddin Jamaluddin; Surahman Surahman (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Good knowledge of the principles, objectives and functions of cooperatives as well as high motivation are expected to increase member involvement in cooperative activities. The aim of this research is to test and analyze the influence of cooperative knowledge and cooperative motivation on cooperative member participation. This research uses a quantitative approach with survey methods. The sampling technique uses saturated sampling and the data collection method uses a questionnaire. The data was processed using SPSS 23 tools. The analysis used included data quality testing, classical assumption testing, multiple linear regression testing, and hypothesis testing. The research results show that cooperative knowledge and cooperative motivation have a positive and significant effect on member participation. Similar results were obtained with the f test which stated that cooperative knowledge and cooperative motivation had a simultaneous effect on member participation.Keywords: Cooperative knowledge, cooperative motivation, member participation, Islamic economics, student cooperatives.